The role of the school counselor in protecting high school students in Medina from intellectual deviations in light of the guiding methods - Al-Mutairi, Ali Sunat (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the most important responsibilities of the student counselor in the development method from the methods of guidance and counseling to immunize high school students from intellectual deviation from the viewpoint of student counselors in secondary schools in Medina, and to identify the most important responsibilities of the student advisor in the method and preventive methods of guidance and counseling to immunize students of the stage Secondary school from intellectual deviation from the viewpoint of student counselors in secondary schools in Medina, the most important responsibilities of the student counselor in the development method of guidance and counseling methods to immunize high school students from intellectual deviation from the viewpoint of student counselors in secondary schools in Medina, and the researcher has followed Descriptive survey approach to achieve the objectives of the study. The study tool was represented by a questionnaire that was distributed to a sample of (73) student counselors from secondary school counselors in Medina. The study found a number of results, the most important of which were: The spread of unemployment among the youth of society leads to their occurrence in many deviations that lead to insecurity, including intellectual deviations, and that ignorance of religion is a common factor for falling into all manifestations of intellectual deviation. Based on the results he suggested The researcher suggested a number of recommendations, the most important of which were: The need for student counselors to coordinate and cooperate with local community institutions with the aim of spreading programs to enhance intellectual security among school students, especially high school students, and to provide student counselors in secondary schools with the financial and technical capabilities necessary to carry out their role in implementing methods of student immunization. Of intellectual perversion.